Edukasi melalui Permainan Snakes and Ladders untuk Mengembangkan Academic Motivation towards a Green Perspective - Hidajat, Helga Graciani; Sumarmi, Sumarmi; Pratiwi, Seli Septiana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
Academic motivation towards a green perspective is academic motivation related to environmental behavior. Low academic motivation towards a green perspective is characterized by behavior that does not understand the need to protect the environment. Problems in the field show that students at SD Negeri Sumbersari 1 Malang lack awareness of environmental love. SD Negeri Sumbersari also does not have education related to environmental awareness. Therefore, the purpose of this community service implementation is to develop academic motivation towards a green perspective in SD Negeri Sumbersari 1 Malang students through a snakes and ladders game with an environmental theme. The method of implementing this community service is the exploration of the theory of academic motivation towards a green perspective; development of green snakes and ladders education; and implementation of green snakes and ladders. The result of this community service is the green snakes and ladders game is able to increase academic motivation towards a green perspective. This is seen from students' understanding of the importance of protecting the environment and carrying out simple environmental actions.